Parasitoid Wasps Associated with Liriomyza trifolii Mortality in Pepper at Baja California Sur, Mexico - Holguín-Peña, Ramón Jaime; Ramírez-Ahuja, María De Lourdes; Medina-Hernández, Diana; Palacios Torres, Rogelio Enrique; Servín-Villegas, Rosalía (Southwestern Entomologist, 2019)
The study provided information, for the first time, on parasitoid species associated with the American serpentine leafminer, Liriomyza trifolii (Burgess) (Diptera: Agromyzidae), in the State of Baja California Sur, Mexico. During 2017, in the agricultural area of El Comitán (24° 07′ 30″ N, 110° 18′ 15″ W), leafminers were abundant during two consecutive cycles of bell and habanero peppers, Capsicum annuum L. and Capsicum chinense Jacq., protected with mesh-shadow systems. The average was 42.2 adults per trap-week and 3.8 mines per leaf, with peaks of 56 adults per trap and 5.2 mines per leaf at 90 days after transplanting. Fifty percent of plants were mined by 45 days after transplanting. Three species of Hymenoptera in Braconidae and Eulophidae families were parasitoids of L. trifolii. Closterocerus cinctipennis Ashmead (Eulophidae: Entedoninae) appeared first, followed by Chrysocharis sp. Forster (Eulophidae: Entedoninae). The last species was Opius dissitus Muesebeck (Braconidae: Opiinae). The parasitism rate was 29% (~40 insects per week) by eulophids and 9% (~12 insects per week) by braconids. New knowledge was provided on the presence and dispersion of L. trifolii at Baja California Sur, and the three species of associated parasitoids.
Keywords: Liriomyza trifolii; Moscas minadoras; Pimiento morrón; Habanero